If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3 = x + -18 Reorder the terms: 3 + 3x = x + -18 Reorder the terms: 3 + 3x = -18 + x Solving 3 + 3x = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 3x + -1x = -18 + x + -1x Combine like terms: 3x + -1x = 2x 3 + 2x = -18 + x + -1x Combine like terms: x + -1x = 0 3 + 2x = -18 + 0 3 + 2x = -18 Add '-3' to each side of the equation. 3 + -3 + 2x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -18 + -3 2x = -18 + -3 Combine like terms: -18 + -3 = -21 2x = -21 Divide each side by '2'. x = -10.5 Simplifying x = -10.5
| -16=x-10 | | 24-6k=6(k-4) | | 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 | | 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x | | 70x^3+112x-1=0 | | 108=-6(x-8)-4x | | 7n=50+24 | | Y-3=-(x-5) | | (5x+y)+(2x+6y)= | | 2(x+9)=26 | | 3*8x=1.5e^2x | | x^4+0.5x^3-6x^2+5=0 | | g-(-7)=13 | | 33=6a+2 | | 20p-(7+2p)= | | z^2+(4+2i)z+(2-3i)=0 |